The Temperature Evaluation of the Buried Hill Geothermal Reservoirs in the Jizhong Depression, Bohai Bay Basin, China. (23rd November 2020) - Dong, Yuyang; Zeng, Jianhui; Zhao, Xianzheng; Wang, Yanu; Chen, Tianhao; Zhang, Yongchao; Feng, Sen
Abstract : The Jizhong Depression is located in the western Bohai Bay Basin, eastern China. The deep strata are mainly composed of carbonate buried hill, and the shallow strata are a mainly siliciclastic deposition. In the present work, the Na-K-Mg triangle diagram and geothermometers were used to investigate the geochemical characteristics of shallow groundwater and reservoir temperature features of three geothermal reservoirs in the depression, including the Ordovician, the Cambrian, and the Precambrian Wumishan Formation. The results showed that the geothermal water in the depression could be divided into three groups: group I, Cl·HCO 3 -Na type; group II, Cl-Na type; and group III, Cl-Na·Ca type. By using the Na-K-Mg triangle diagram, group II and group III geothermal water samples were identified as the partially equilibrated water, whose temperature of the geothermal reservoir can be calculated based on the cation geothermometers. The ranges of the calculated temperature of the shallow strata and the deep strata are 91 146°C and 147 176°C, respectively. It has the good results obtained with some cation geothermometers in a geothermal system hosted in carbonate rocks like the studied area. The analysis workflow and calculation data obtained in this work contribute to the evaluation of the temperature field and the exploration and development of the geothermal resources in the Bohai Bay Basin.